Street space design for bendi in the urban area of a ternate city - Arifah Pasri, Andi; ., Sabaruddin; Gaus, Abdul; Amir Sultan, Mufti; ., Najamuddin (International Journal of Engineering and Technology, 2020)
Spatial planning is very important because it is a public space so whether or not a street space will affect all road users. Structuring street space is to increase user experience so that the best place of public space is achieved.To get the best place, we need to accommodate and clearly define each user of the space. Bendi as a mode of transportation certainly uses street space as a means of motion space. And it requires a clear definition of the movement of the bendi in a physical order that can prevent violations of the rights of other street users both pedestrians and motorized vehicles.The purpose of this study is how the standard of road spatial planning for bendi. The method used in this study is the collection of field data through qualitative descriptive analysis with several indicators, namely Characteristics and space for bendi, spatial planning standards, street space settings. The design concept of bendi lane is proposed in 2 types, namely a special lane with a straight line divider on the Hasan Esa street, the Pahlawan revolusi street, and the Djabar Syah street and integration on the Ahmad Yani street and the Nukila street.Â